Associations between diabetes mellitus and the risk of hepatocellular carcinoma in Asian individuals with hepatitis B and C infection: systematic review and a meta-analysis of cohort studies. Issue 2 (March 2022) - Yang, Chao; Wan, Min; Lu, Yifei; Yang, Xian; Yang, Ligang; Wang, Shaokang; Sun, Guiju
Abstract : We aim to further analyze and compare associations between diabetes mellitus and the risk of hepatocellular carcinoma (HCC) in Asian individuals with hepatitis B or C virus infection by conducting an updated meta-analysis of cohort studies. Literature search was conducted in PubMed, Scopus, Web of Science, and Cochrane Library from the beginning of indexing for each database to January 1, 2020. A total of 22 articles met the inclusion criteria, in which 18 were cohort studies and 4 were case-control studies. We identified eight cohort studies and three case-control studies that presented results on diabetes mellitus and the risk of HCC in Asian subjects with hepatitis B virus (HBV) infection: the cumulative relative risk (RR) with 95% confidence interval (CI) was 1.37 (95% CI: 1.24 to 1.51; I 2 = 27.8%) for cohort studies and cumulative odds ratio (OR) with 95% CI was 1.99 (95% CI: 0.73 to 5.48; I 2 = 88.4%) for case-control studies. Thirteen cohort studies and two case-control studies presented results on the association between diabetes mellitus and the risk of HCC in Asian subjects with hepatitis C virus (HCV) infection: the RR with 95% CI was 1.76 (95% CI: 1.42 to 2.17; I 2 = 62.8%) for cohort studies and OR with 95% CI was 1.77 (95% CI: 1.18 to 2.64; I 2 = 0.0%) for case-control studies. In summary, our meta-analysis strongly supports the association between coexistent HCV and diabetes with the increasing risk of HCC; although the results equally support diabetes mellitus being significantly associated with increased risk of HCC among patients with HBV infection, this correlation is weaker than the former. Abstract : Supplemental Digital Content is available in the text.